2022
DOI: 10.48550/arxiv.2205.07834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patchy nightside clouds on ultra-hot Jupiters: General Circulation Model simulations with radiatively active cloud tracers

Thaddeus D. Komacek,
Xianyu Tan,
Peter Gao
et al.

Abstract: The atmospheres of ultra-hot Jupiters have been characterized in detail through recent phase curve and low-and high-resolution emission and transmission spectroscopic observations. Previous numerical studies have analyzed the effect of the localized recombination of hydrogen on the atmospheric dynamics and heat transport of ultra-hot Jupiters, finding that hydrogen dissociation and recombination lead to a reduction in the day-to-night contrasts of ultra-hot Jupiters relative to previous expectations. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…Coupled cloud formation models to the GCM in the UHJ regime (e.g. Komacek et al 2022) will be enlightening to see if TiO can be cold trapped in the case of WASP-121b. Potential cold trapping of TiO was investigated for HD 209458b in Parmentier et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled cloud formation models to the GCM in the UHJ regime (e.g. Komacek et al 2022) will be enlightening to see if TiO can be cold trapped in the case of WASP-121b. Potential cold trapping of TiO was investigated for HD 209458b in Parmentier et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…This likely the case for some UHJ planets (e.g. Helling et al 2021;Komacek et al 2022), with clouds mostly confined to the nightside hemisphere. However, due to the significant added computational expense of modelling clouds in hot Jupiter GCMs (e.g.…”
Section: Gcm Modellingmentioning
confidence: 91%
“…Such clouds form at pressures of 10 βˆ’2 -10 βˆ’3 bar depending on the temperature, consistent with our opacity decks for the night side of log(𝑃 cl /bar) = βˆ’2.08 +0.44 βˆ’0.53 (evening side, πœ™ = βˆ’0.04 -βˆ’ 0.02) and log(𝑃 cl /bar) = βˆ’3.33 +0.80 βˆ’0.91 (morning side, πœ™ = 0.02 -0.04). Recent work has also shown that patchy clouds may be present on the night side of UHJs but that they only weakly affect terminator observations (Komacek et al 2022).…”
Section: Opacity Deckmentioning
confidence: 99%
“…Including winds into atmospheric models is also of particular importance given that there are also a growing number of high-resolution studies which have constrained these on the terminator (Brogi et al 2016;Flowers et al 2019;Seidel et al 2021). In addition, recent work has also shown that cloud formation on the night side of UHJs is strongly dependent on the atmospheric dynamics (Komacek et al 2022) and these clouds can affect phase-dependent emission spectra.…”
Section: Introductionmentioning
confidence: 99%